Masyarakat Dani di Irian Jaya: Adat-Istiadat dan Kesehatan - Meutia F. Swasono; M. Junus Melalatoa; Sri Murni; Ukke Kosasih (Antropologi Indonesia, 1997)
This article is a result of ethnographic study on health problems among the Dani in Baliem valley, Irian Jaya. The study shows that some behaviors are not always good for Dani's physical and mental health. It is apparent in their daily activities such as livelihood, housing condition, ritual, etc.